High‐Temperature Solid‐State Synthesis and Electrochemical Properties of Transition Metal Sulfides for Thermal Batteries. Issue 4 (9th February 2022) - Hu, Jing; Wang, Xin-Liang; Guo, Hao; Yang, Ming; Yuan, Jin-Xiu; Chu, Ying; Zhao, Li-Li
Abstract : Transition metal sulfide is the most widely used cathode material for thermal batteries. The development of modern weapons requires higher quality and output of transition metal sulfide cathode materials. However, the current synthesis processes have some limitations for large‐scale industrial production due to the long production cycle and low production efficiency. Herein, by controlling the synthesis temperature and adopting a high‐temperature solid‐state method, sulfide FeS2, CoS2, and NiS2 with single‐phase and good crystalline structure are synthesized. This method with a simple production process, short production cycle, and high single output is suitable for engineering production. Hence, guidance for large‐scale industrial synthesis of pure phase FeS2, NiS2, and CoS2 is provided, embodying important scientific significance and application value. Abstract : Transition metal sulfides with single‐phase and good crystalline structure are prepared by a high‐temperature solid‐state method via controlling the synthesis temperature. The optimum synthesis temperatures of FeS2, CoS2, and NiS2 are 580, 640, and 620 °C, respectively. The simple method is suitable for the large‐scale industrialization of transition metal sulfides, and provides matching cathode materials for a thermal battery system.